Electronic Structure of Quantum Confined Atoms and Molecules - Sen, K.D (Springer International Publishing : Imprint: Springer, 2014)
The present volume is a collection of review articles highlighting the fundamental advances made in the area of spatially confined simple atoms and molecules with focus on their electronic structure. The contributed chapters are conjoined together to provide a standard reference book in this rapidly growing area of interdisciplinary research spanning chemistry, physics, computational quantum chemistry and material science.